Enhancement of electric field‐induced strain in BaTiO3 ceramics through grain size optimization. Issue 2 (30th September 2014) - Tan, Yongqiang; Zhang, Jialiang; Wang, Chunlei; Viola, Giuseppe; Yan, Haixue
<x xml:space="preserve">Abstract</x> The effect of grain size on electric field‐induced strain in BaTiO3 ceramics was explored. The unipolar strain first increases and then decreases with increasing grain size with a peak of 0.28% around 4.5 µm. Small grains have more recoverable non‐180° domains, but also more restriction from grain boundaries, while coarse grains have less restriction from grain boundaries, but less recoverable non‐180° domains. Thus, only ceramics with intermediate grain size can show large electric field‐induced strain at electrical loading regime conditions.